Bullying in the Military: A Review of the Research on Predictors and Outcomes of Bullying Victimization and Perpetration. (3rd July 2021) - Stuart, Jaimee; Szeszeran, Nicholas
Abstract: Bullying is defined as repeated, intentionally harmful acts against an individual in which the victim feels coerced, degraded, humiliated, threatened, intimidated, or frightened and where there is power imbalance between the victim and perpetrator. Extensive, research in workplace context indicates that bullying has wide-ranging impacts for those who are victimized, for the culture of the working environment, and for the organization itself. However, the literature on workplace bullying within the military has yet to be thoroughly reviewed due to several complexities in assessing the prevalence of these behaviors and making comparisons across national contexts. Bullying in the military is a particularly important issue given the unique working environment in which this occurs. This article presents a review of the international literature available in English on bullying in the military and describes two major themes which were identified from this review; the nature of bullying in the military its impacts (who is most likely to be a victim or perpetrator) and the cultural and workplace factors in the military context that contribute to the experience of bullying (values of hierarchy, power and dominance, conformity, and leadership). The implications for bullying interventions within military settings are discussed in relation to these findings.